Ultraviolet B irradiation in the prevention of alloimmunization in a dog platelet transfusion model. Issue 6 (17th May 2016) - Slichter, Sherrill J.; Abrams, Kraig; Gettinger, Irena; Christoffel, Todd; Gaur, Lakshmi; Latchman, Yvette; Nelson, Karen; Pellham, Esther; Bailey, S. Lawrence; Bolgiano, Doug
Abstract : BACKGROUND: Alloimmune platelet (PLT) refractoriness remains a significant problem for chronically transfused patients with thrombocytopenia. STUDY DESIGN AND METHODS: In a dog PLT transfusion model, we evaluated ultraviolet B irradiation (UV‐B) of donor PLTs—either alone or in combination with centrifuge leukoreduction (C‐LR) or filtration leukoreduction (F‐LR)—to prevent refractoriness to donor PLTs and to induce tolerance to standard (STD) PLTs from the same donor or to tertiary donors. RESULTS: Recipient acceptance rates for C‐LR donor PLT transfusions were 14%, F‐LR were 33%, and UV‐B irradiated were 45% with no significant differences among the treatments given to the donor's PLTs. Adding UV‐B irradiation to C‐LR or F‐LR PLTs increased acceptance rates to 50 and 68% (p = 0.02 and p = 0.05), respectively, comparing single treatments to the combined treatments. After a recipient had accepted any type of UV‐B–treated donor PLTs, specific tolerance to subsequent transfusions of the same donor's STD PLTs averaged 65%. Nonspecific tolerance to third‐party donor's STD PLTs averaged 36% if they had accepted their initial donor's treated PLTs but was only 4% (p < 0.001) if they had rejected these PLTs. CONCLUSION: Combining UV‐B irradiation with a method of leukoreduction produces additive effects on prevention of alloimmune PLT refractoriness.